Rig-ʼdzin Rgod-ldem gyi Brgyag rṅan daṅ sger gsol gyi rim pa ʼdod don lhun grub źes bya ba bźugs paʼi dbu phyogs so - Rgod-kyi-ldem-ʼphru-can, Gter-ston, 1337-1408 (Ngagyur Nyingmay Sungrab, 1981)
Rituals for the propitiation of the host of protective deities through the burning of fragrant substances and the offering of libations of beer and tea.